Digital Da'wah and Quranic Interpretation: Opportunities, Distortions, and Ethics in the Spread of Interpretations on Social Media - Armita, Pipin (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
Digitalization has changed the face of Islamic preaching and dissemination of knowledge, including the interpretation of the Qur'an, which now reaches a broad audience through various social media platforms. This transformation presents significant opportunities in religious education, but also poses serious challenges in the form of distortion of meaning and oversimplification in the presentation of interpretations. This study aims to examine the dynamics of disseminating interpretations of the Qur'an on social media from three main aspects: opportunities, potential distortion, and ethics of dissemination. With a qualitative-analytical approach, this study relies on digital documentation and literature studies of interpretation content spread on platforms such as YouTube, Instagram, and TikTok. The data is reviewed in depth to understand the methodological tendencies, narratives, and scientific responsibilities in the presentation of interpretations. The results of the study show that although social media can increase accessibility and attract the interest of the younger generation in interpretations, there is a high risk of the dissemination of interpretations that do not go through proper scientific procedures, ignore the context of the verses, and pay little attention to differences in the views of scholars. In addition, ethics in disseminating interpretations are often ignored, either in the form of plagiarism, provocation, or misleading language. Therefore, this study emphasizes the importance of ethical guidelines and the active role of religious institutions in overseeing the dissemination of digital interpretation of the Qur'an so that it remains within the scientific and Sharia corridor. This study emphasizes the importance of synergy between digital innovation and the integrity of interpretation science in presenting relevant, credible, and responsible da'wah in the information era.